Comparative Study on Paddle-wheel Aerators Using Electric Motors and Diesel Engines in Pacific White Shrimp (Litopenaeus vannamei) Culture Ponds - Wara Taparhudee; Mathud Benjaprasertsri; Bunyat Sattiti (Agriculture and Natural Resources, 2007)
The purpose of the study was to compare water velocity, water quality, soil quality, production and energy costs of two paddle-wheel aerator systems, operated by electric motors and diesel engines, commonly used in shrimp farms. The study was separated into two experiments. The first experiment focused on water velocities produced by paddle wheel aerators using different rotational speeds. Research found that water velocity could not be measured at a distance of 25 meters away from the front of both systems’ aerators at all the different speeds. The second experiment was performed in an intensive Pacific white shrimp farm. Three of the ponds were aerated using six long-armed paddle-wheel aerators, powered by two 11 hp diesel engines. The other three were aerated by six long-armed paddle-wheel aerators and used four 2 hp electric motors. Each paddle-wheel aerator was installed 25 meters apart. The results showed the ponds powered by the diesel engines obtained greater average production and higher average profit compared to the pond powered by the electric motors. This was because the paddlewheel aerators using diesel engines could produce greater water velocity than the electric motors system. Consequently, they provided more dissolved oxygen to the water, cleaner feeding area, and removed the waste and sediment to the center of the pond more efficiently, which are important factors for the success of shrimp culture.